New Treatment Paradigms Defined for Chronic Lymphocytic Leukemia - Moran, Mollie (J Adv Pract Oncol, 2017)
Within the past 3 years, the FDA has approved five new treatment options for patients with CLL. While these advances improve patient outcomes and the quality of care, there is a need for advanced practitioners to stay up to date and informed in order to translate these advances into the clinical setting.